ترجمة المصطلح المتخصص بين التنظير والتطبيق كتاب "Translation Studies" لسوزان باسنيت، ترجمة فؤاد عبد المطلب أنموذجا : Translation of specialized terminology between theory and practice (“Translation Studies” author Susan Bassnett and translation of Fuad Abdul - بساس عبد السلام; بوخميس ليلى (Maalim, 2022)
The aim of this study is to highlight the essence of specialized terms and the scientific methods to create them. We have based our study on a descriptive analytical method applied on a scientific book entitled Translation Studies as corpus. Terminologists establish new terms according to specific rules, the users of the terminology among them translators should not underestimate this effort by sidestepping it. In this context we tried to answer the following questions: What are the methods and techniques involved in terminology elaboration? Did Abdul Muttalib take support of experts and their dictionaries? Or did he choose another method in the translation of the terms of the corpus? The results of the study underlined the significance of specialized terms in the transfer of science and knowledge.